Spatial Analysis of Land Use Land Cover Change At Takhatpur Nagar Panchayat of Bilaspur District In Chhattisgarh - Bhagat, Sanjeev Kumar; Singh, P. R; Kumar, Dilip (International Journal of Computer Sciences and Engineering, 2025)
Land use is a primary indicator of the extent and degree to which man has modified the land resources. For the present study Takhatpur nagar panchayat of Bilaspur district of Chhattisgarh state was selected randomly. The Google earth, satellite images and GIS software (QGIS /SAGA) were used for the development of land use and land cover classes and subsequently for change detection analysis of the study area. From the findings, it was observed that the agricultural land of Takhatpur nagar panchayat was decreased upto27.883 hectare. The total 4.283 hectare rural build up and total 23.30 hectare urban build up area of Takhatpur nagar panchayat was increased during last 10 years span of time